Human platelet lysate can replace fetal calf serum as a protein source to promote expansion and osteogenic differentiation of human bone-marrow-derived mesenchymal stromal cells - Karadjian, Maria; Senger, Anne-Sophie; Essers, Christopher; Heller, Raban; Fellenberg, Jörg; Westhauser, Fabian (Cells, 2020)
Fetal calf serum (FCS) is frequently used as a growth factor and protein source in bone-marrow-derived mesenchymal stromal cell (BMSC) culture media, although it is a xenogenic product presenting multiple disadvantages including but not limited to ethical concerns. A promising alternative for FCS is human platelet lysate (hPL), which is produced out of human platelet concentrates and happens to be a stable and reliable protein source. In this study, we investigated the influence of hPL in an expansion medium (ESM) and an osteogenic differentiation medium (ODM) on the proliferation and osteogenic differentiation capacity of human BMSC. Therefore, we assessed population doublings during cell expansion, performed alizarin red staining to evaluate the calcium content in the extracellular matrix and determined the activity of alkaline phosphatase (ALP) as osteogenic differentiation correlates. The proliferation rate of BMSC cultured in ESM supplemented with hPL exceeded the proliferation rate of BMSC cultured in the presence of FCS. Furthermore, the calcium content and ALP activity was significantly higher in samples incubated in hPL-supplemented ODM, especially in the early phases of differentiation. Our results show that hPL can replace FCS as a protein supplier in cell culture media and does not negatively affect the osteogenic differentiation capacity of BMSC.